e-STC For Site Requisition Machinery Spare Part Order - Noraziah Hamid; Nur Azyyati Fari’ah Farizal Haryadi, (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
Procurement Department at Pembinaan Tetap Teguh Jentera (PTTJ) basically manage all machineries at the site and responsible for internal department request, dealing with suppliers, coordinating, and monitoring purchases especially in documentation for purchase spare part machineries and equipment’s order. The existing method used for machinery spare parts orders is not systematic and difficult to track between the Workshop Department and The Procurement Department, resulting in overlooking, double order, delay payment to suppliers, and blocked orders by suppliers. Therefore, the aim of the study is to develop the systematic tracking centre (e-STC) for site requisition machinery spare part order using wix.com at PTTJ for more systematic and efficient of purchase Invoices and Delivery Orders (DO) and payments to suppliers. There are three objectives to be studies, first is to identify the need of systematic tracking centre for site requisition machinery spare part orders at PTTJ. Secondly is to develop the e-STC for site requisition machinery spare part orders at PTTJ using wix.com and finally is to test the effectiveness of systematic tracking centre (e-STC) for site requisition machinery spare part orders at PTTJ. Objective 1 and 3, used quantitative method conducted by survey and objective 2 use wix.com. Data Analysis uses SPSS and Excel Solution Online. The results for objective 1 showed that the current method; average mean is very low in every constraint element; <1.5 average mean and was resulted for current method, easy to track order element. Result for objective 2 show that e-STC for site requisition machinery spare part orders at PTTJ using wix.com successful to developed. Meanwhile, result for objective 3 show that > 90% respondents agree the e-STC for site requisition machinery spare part order is systematic. Paired T Test showed the effectiveness element of e-STC for site requisition machinery spare part order for resulted as 2.69 in differences average mean; High in agree interpretation. The conclusion, e-STC is a systematic and efficient medium for purchase Invoices and Delivery Orders (DO) and payments to suppliers and needs to be implemented for site requisition machinery spare part orders at PTTJ.